2023
DOI: 10.1080/20008066.2023.2205667
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical activity and individual mental health after traumatic events: a systematic review

Abstract: Background: Traumatic events can cause social tension, anxiety, panic and other psychological crises, and can even cause post-traumatic stress disorder (PTSD) and suicide. Physical activity has a good role in promoting mental health, and has a great application prospect in individual psychological intervention after traumatic events. However, no systematic review of the relationship between physical activity and individual mental health after traumatic events affecting many people has been published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…However, after actively coping with and overcoming these difficulties, university students can form a more stress-resistant and resilient state of mind, which can help them to effectively cope with and adapt to adverse stress events when facing similar situations again in the future and maintain a more positive attitude towards life and their emotional states. In addition, university students with higher psychological resilience can use multiple problem-solving strategies to alleviate the adverse effects of stressful events in physical activity, maintain their psychological health, and have less anxiety and depression when facing problems [ 54 ]. In general, students with higher resilience are less likely to experience anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after actively coping with and overcoming these difficulties, university students can form a more stress-resistant and resilient state of mind, which can help them to effectively cope with and adapt to adverse stress events when facing similar situations again in the future and maintain a more positive attitude towards life and their emotional states. In addition, university students with higher psychological resilience can use multiple problem-solving strategies to alleviate the adverse effects of stressful events in physical activity, maintain their psychological health, and have less anxiety and depression when facing problems [ 54 ]. In general, students with higher resilience are less likely to experience anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…However, it belongs to prerequisite-focused emotion regulation, re-processing the causes of emotions. It mobilises more of one’s cognitive processing system to reappraise the explanations of the causes of emotions and changes one’s understanding of emotional events [ 54 ]. When there are more positive than negative emotions in daily life, it can lead to a more positive evaluation of one’s quality of life and, thus, provide a greater sense of perceived well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our study was the lack of comprehensive factors investigated, such as eating habits, sleep quality, and physical activity. Those factors have been proven to be associated with the physical tness and mental health of individuals [40][41][42], and need to be further adjusted in subsequent models. Moreover, the cross-sectional design of our study may limit the accuracy of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Self-perception may be an important target for therapy. Lifestyle factors Wang et al ( 2023 ) Relationship between physical activity and individual mental health after traumatic events: a systematic review Regular physical activity following traumatic events was associated with better well-being and fewer psychological symptoms. Physical activity may also buffer against symptom development and help maintain physical and mental health.…”
Section: In This Issuementioning
confidence: 99%
“…Two papers in this series focus on the impact of diet and exercise on post trauma functioning . Physical activity and its relation to psychological functioning was the focus of a review by (Wang et al, 2023 ) entitled ‘Relationship between physical activity and individual mental health after traumatic events: a systematic review’. They concluded that regular physical activity can be a protective factor against the development of symptoms as well as improve mental health functioning following exposure to traumatic events.…”
Section: In This Issuementioning
confidence: 99%